2016
DOI: 10.1088/0952-4746/36/2/363
|View full text |Cite
|
Sign up to set email alerts
|

Adapting clinical gamma cameras for body monitoring in the event of a large-scale radiological incident

Abstract: After a release of radionuclides, accidental or otherwise, there will be an urgent need to identify members of the general public who have received a significant intake of radioactive material, sufficient to require medical treatment or further investigation. A large number of people could be contaminated in such an incident. For gamma-ray emitting radionuclides this screening could be carried out using gamma camera medical imaging systems, such as those that are present in many large UK hospital sites. By mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…In the second step, the W, X, Y, and Z sub-regions were transformed into E, F, G, and H, respectively, by rotating 180°, as shown in (4). where…”
Section: Matrix Function Of Mpa-muramentioning
confidence: 99%
See 1 more Smart Citation
“…In the second step, the W, X, Y, and Z sub-regions were transformed into E, F, G, and H, respectively, by rotating 180°, as shown in (4). where…”
Section: Matrix Function Of Mpa-muramentioning
confidence: 99%
“…The main nuclides released included Mo-99 (140.5 keV), Ce-141 (145 keV), Ce-144 (133 keV), I-131 (365 keV), Cs-137 (662 keV), Cs-134 (604 keV, 795 keV), Zr-95 (724.1 keV, 756.7 keV), Mn-54 (834.85 keV), and Co-60 (1173 keV, 1332 keV), [1][2][3] and enter the human body through breathing, drinking, eating, and open wounds. Therefore, it is imperative to urgently carry out the screening of internal radioactive contamination as early as possible after a nuclear accident [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency in detecting higher photon energies decreases rapidly with decreasing thickness of the NaI crystal, and several radionuclides of concern in RN events emit gamma rays of higher energies, e.g. 662 keV from 137 Cs, and 1173 keV and 1332 keV from 60 Co. Another problem is the energy window allowed in commercial gamma cameras, which is often restricted to below 550 keV [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that, despite the above-mentioned drawbacks, the use of gamma cameras as a complement to WBCs for the estimation of the activity of the radionuclides that can be expected following an RN event, is feasible [6][7][8][9][10]. In the case of an RN event, the imaging capability is of minor interest compared to the ability to quantify the internal contamination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation